Spoilage Indices in Chill-Stored Rohu Steaks Extracted with Different Concentrations of Trichloroacetic Acid - Raghunath, M R; Umalatha, H; Sridhar, N; Hemaprasanth, K; Gangadhar, B; Jayasankar, P (Fishery Technology, 2025)
Spoilage or freshness indices are extensively used in fish processing industry and research. Although frequently employed, the index total volatile basic nitrogen (TVBN) in freshwater fish does not correlate well with storage. Rohu (Labeo rohita) steaks treated with chlorine dioxide (ClO2 ) and chill-stored in ice for 14 days were extracted with differing strengths of trichloroacetic acid (2, 4, 6 and 8% TCA) and analyzed for TVBN as well as biuret +ve and folin +ve substances. TVBN, biuret +ve and folin +ve substances did not increase significantly during the first 10 days, but increased sharply thereafter in both control and ClO2 treated steaks. Greater amounts of TVBN and biuret +ve substances were extracted at lower TCA concentrations. Biuret +ve substances extracted by 2% TCA from both treated and control steaks showed significant proportional changes with storage, but decreased in the former and increased in the latter. Sensory changes in the steaks appeared as early as the 4th day and darkening of the lateral line red meat was the most easily noticed and off-odours by the 6th day. Biuret +ve substances extracted at low TCA concentrations may hold promise as spoilage indices, but need further investigation.